Community-acquired Staphylococcus aureus meningitis in adults. Issue 3 (March 2023) - van Soest, Thijs M.; Søndermølle, Maria Birgitte; Brouwer, Matthijs C.; Chekrouni, Nora; Larsen, Anders Rhod; Petersen, Andreas; van Sorge, Nina M.; Nielsen, Henrik; van de Beek, Diederik; Bodilsen, Jacob; ,
Summary: Background: Staphylococcus aureus is an uncommon cause of community-acquired bacterial meningitis. We aimed to describe patients with this disease. Methods: We evaluated clinical characteristics and outcome of adults with community-acquired S. aureus meningitis from prospective nationwide cohort studies from Denmark (2015-2020) and the Netherlands (2006-2021). Whole genome sequencing of S. aureus isolates was performed to evaluate the potential association between clonal complex and clinical characteristics. Results: We evaluated 111 episodes of community-acquired S. aureus meningitis: 65 from Denmark and 46 from the Netherlands. The median age was 66 years (interquartile range [IQR] 50-74) and 43 of 111 patients were female (39%). Concomitant infectious foci were found in 95 of 107 patients (89%), most commonly endocarditis (53 of 109 [49%]) and spondylodiscitis (43 of 109 [39%]). The triad of neck stiffness, altered mental status (Glasgow Coma Scale score <14), and fever was present in only 18 of 108 patients (17%). Surgery was performed in 14 of 33 patients (42%) with spondylodiscitis and 26 of 52 (50%) with endocarditis. A favorable outcome (Glasgow Outcome Scale score 5) occurred in 26 of 111 patients (23%), while 39 (35%) died. The most common bacterial clonal complexes (CC) were CC30 (16 [17%]), CC45 (16 [17%]), CC5 (12 [13%], and CC15 (10 [11%]); no associations between CCs and concomitant foci or outcome were found. Conclusions: Community-acquired S. aureus meningitis is a severe disease with a high case fatality rate, occurring mainly in patients with concomitant endocarditis or spondylodiscitis.